Natural Beauty. Issue 2 (20th November 2019) - Benson, Peter
Abstract: This is a story of young love. A boy raised on baseball near the Bronx meets a farm girl who works and rides. Dorm days and nights are alternative music and playing hooky. Summer trips to the farm get him hooked. Set across a culture of higher education, this work of creative nonfiction with a soundtrack describes intimacies of cattle farming, horseback riding, campus life, and domesticity. About natural and cultural aesthetics, it is also an almanac entry for agrarian queerness and immense alternatives.